Demographic Problems in the Northern Regions of the Republic of Kazakhstan - K. Bodaukhan; N. Shaikenova; A. Shilmanova; M. Bayandin; Zh. Kochiygit (Экономика: стратегия и практика, 2024)
This article aims to analyse demographic and migration processes in Kazakhstan, focusing on identifying their impact on society’s economic, political and social aspects. The work methodology is based on comparisons and system-structural methods, such as control, generalization, systematization, logical analysis, and synthesis. The study used two main groups of indicators for 1990-2021. The first group included comparative indicators, such as the relative size of the population structure, the intensity and relative proportions of the structure, and the proportions of the urban and rural population. The second group included migration indicators, such as the number of arrivals to the settlement, the number of departures from the settlement, and absolute migration growth or balance. The study results reveal regional differences, especially in the context of migration processes. There is a negative balance of internal migration and high rates of population decline in the northern regions. In comparison, the southern regions are experiencing population growth, which poses new economic and social challenges. It is predicted that by 2050, the population of the south of regions will increase significantly. The authors emphasize the importance of an integrated approach to solving demographic problems, including improving well-being, providing affordable health care and developing effective demographic policies. In conclusion, it is noted that successfully overcoming demographic challenges requires balanced economic and social measures.